Utilizing Smart Ladder Media to Enhance Student Learning Outcomes on Length Units in Third-Grade Elementary School - Ripo, Helena Enselmini; Ndori, Vinsensius Herianto; Dhema, Magdalena (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2024)
This study aims to assess the mathematics learning outcomes of third-grade students at MIS Muhammadiyah Darussalam Waioti, Sikka (a private elementary school) on the topic of length units using the "smart ladder" media. This research follows a Classroom Action Research (CAR) approach, employing both qualitative and quantitative methods. It comprises two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study are third-grade students. Data collection methods include tests and observation. Research instruments consist of an observation sheet for assessing student engagement and a test to measure learning outcomes. The findings reveal that mathematics learning using the smart ladder media showed improvement from Cycle I to Cycle II, with the learning outcome mastery level reaching 18% in Cycle I and student engagement observed at 44%. In Cycle II, the mastery level increased to 94%, with student engagement reaching 93%. These results suggest that the use of the smart ladder media for teaching length units effectively enhances the learning outcomes of third-grade students at this school.